Pre-lacteal feeding practice and associated factors among mothers having children less than two years of age in Aksum town, Tigray, Ethiopia, 2017: a cross-sectional study - Tekaly, Girmay (BMC Pediatr, 2018)
BACKGROUND: Pre-lacteal feeding has continued as a deep-rooted nutritional malpractice in developing countries. Pre-lacteal feeding is a barrier to the implementation of optimal breastfeeding practices and increases the risk of neonatal early-life diseases and mortality. Therefore, the aim of this study was to assess pre-lacteal feeding practice and associated factors among mothers having children less than 2 years of age in Aksum town, central Tigray, Ethiopia. METHODS: A community-based cross-sectional study was conducted to interview 477 mother-child pairs by systematic random sampling technique. Data were collected through interviewer-administered semi-structured questionnaires. Data were coded, entered, cleaned and edited using EPIDATA version 3.1 and export to SPSS Version 22.0 for analysis. To identify the significant variables binary logistic regression were employed. Variables with p-value < 0.05 at 95% CI in multivariate logistic regression were considered statistically significant. RESULT: The prevalence of pre-lacteal feeding in Aksum town was 10.1% (95% CI: 7.3%, 13%). Mothers with no previous birth (AOR: 2.93(95% CI:1.21,7.09)), birth spacing less than 24 (AOR: 2.88(95% CI: 1.15,7.25)), colostrum discarding (AOR: 6.72 (95% CI: 2.49,18.12)), less than four anti natal care follow up (AOR: 10.55 (95% CI: 4.78,23.40)), those who underwent cesarean section (AOR: 4.38 (95% CI:1.72,11.12)) and maternal believe on purported advantage of pre-lacteal feeding (AOR: 3.36 (95%CI: 1.62,6.96)) were more likely to practice pre-lacteal feeding to their infants. CONCLUSIONS: Pre-lacteal feeding is still practiced in the study area. Childbirth spacing, colostrum discarding, antenatal Care follow up, maternal belief in pre-lacteal feeding was contributing factors for practicing of pre-lacteal feeding. Coordination and sustaining the existing strategies and approaches are recommended to give emphasis on the nutritional value of colostrum and anti-natal care follow up.